Motor behavior correlates with striatal [18F]-DOPA uptake in MPTP-lesioned primates - Kortekaas, R.; Eshuis, S.A.; Andringa, G.; Cools, A.R.; Leenders, K.L. (Neurochemistry international, 2013)
[Display omitted] ► Motor behavior correlates with striatal [18F]-DOPA uptake in MPTP lesioned primates. ► MPTP lesioned monkeys have lower radioactivity concentrations in the striatum. ► A negative correlation exists between uptake of [18F]-F-DOPA and motor behaviour. ► Behavioural scoring is a sensitive method to monitor dopaminergic degeneration. ► [18F]-F-DOPA PET is a sensitive method to monitor dopaminergic degeneration. The MPTP-lesioned monkey is considered as the best animal model for Parkinson’s disease (PD). It has damage to dopaminergic cell groups and motor dysfunction similar to that seen in PD. Correlations between these two parameters have been described but there is a lack of formal statistical analyses on dopaminergic function as assessed by [18F]-F-DOPA PET and objectively rated motor behavior in longitudinal experiments. Eight rhesus monkeys received two MPTP infusions: first in one carotid artery, and after eight weeks in the other. Motor behavior and [18F]-F-DOPA uptake were measured at three stages: baseline, unilateral and bilateral. We correlated movement with radiotracer uptake across these three stages. MPTP caused the expected parkinsonian motor signs which were accompanied by lower radioactivity concentrations in the striatum. There were significant correlations between dopaminergic function and behavior. In conclusion, striatal [18F]-F-DOPA uptake correlates inversely with the severity of motor impairment in MPTP-lesioned non-human primates. Both behavioral scoring and [18F]-F-DOPA PET scans are useful and sensitive methods to monitor dopaminergic degeneration within subjects.